2005
DOI: 10.1021/jm050557v
|View full text |Cite
|
Sign up to set email alerts
|

2,5-Diketopiperazines as Potent, Selective, and Orally Bioavailable Oxytocin Antagonists. 2. Synthesis, Chirality, and Pharmacokinetics

Abstract: A short stereoselective synthesis of a series of chiral 7-aryl-2,5-diketopiperazines oxytocin antagonists is described. Varying the functionality and substitution pattern of substituents in the 7-aryl ring and varying the chirality of this exocyclic ring have produced potent oxytocin antagonists (pK(i) > 8.5). SAR and pharmacokinetic profiling of this series of (3R,6R,7R)-2,5-diketopiperazines together with the introduction of an ortho F group in the 7-aryl ring to improve rat pK has culminated in the 2',4'-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 23 publications
0
64
0
Order By: Relevance
“…The DKP scaffold is widely found in compounds of biological interest and could serve as a drug template with appropriate arrayed pharmacophores. To this point, studies showed that the replacement of a DKP cis-amide bound with structurally similar (z)-alkene units could provide DKP mimetics (16) as novel templates for creating drug-like structures [50][51][52][53][54]. Therefore, adequate linear dipeptide derivatives could act as prodrugs for DKP-based drugs.…”
Section: Peptide Carriers A) Peptide Cyclization and Prodrug Designmentioning
confidence: 99%
“…The DKP scaffold is widely found in compounds of biological interest and could serve as a drug template with appropriate arrayed pharmacophores. To this point, studies showed that the replacement of a DKP cis-amide bound with structurally similar (z)-alkene units could provide DKP mimetics (16) as novel templates for creating drug-like structures [50][51][52][53][54]. Therefore, adequate linear dipeptide derivatives could act as prodrugs for DKP-based drugs.…”
Section: Peptide Carriers A) Peptide Cyclization and Prodrug Designmentioning
confidence: 99%
“…5). 24 The X-ray crystal structure of 19 showed that the 3 and the 6 substituents are on the same face of the DKP ring, which is in a puckered conformation and confirmed the stereochemistry of the 3, 6, and 7 substituents as RRR.…”
Section: Comparison Of Crystal Structures Of Ot and 25-diketopiperazmentioning
confidence: 78%
“…4). 24 A four-carbon branched alkyl, isobutyl, or secbutyl was found to be optimal for potency at the 3-position, whereas increasing the size of the group to benzyl or decreasing it to methyl resulted in a reduction in potency. It was also confirmed that an aryl group was required at the 7-position as alkyl or cycloalkyl substituents at this position were at least 100-fold less potent than phenyl.…”
Section: Template Discovery Synthesis and Initial Sarmentioning
confidence: 96%
See 2 more Smart Citations